2019
DOI: 10.1024/0301-1526/a000802
|View full text |Cite
|
Sign up to set email alerts
|

Power-injectable totally implantable venous access devices – analysis of success and complication rates of ultrasound-guided implantation and a patient satisfaction survey

Abstract: Summary. Background: To retrospectively evaluate the success rates, peri-interventional, early and late complications and patient satisfaction associated with power-injectable totally implantable venous access devices (TIVAPs). Patients and methods: Between April 2011 and March 2016, a total of 1,203 TIVAPs were implanted in 1,169 patients. Ultrasound-guided, fluoroscopically controlled implantation was performed through the subclavian or internal jugular vein. The systematic analysis focused on the rate of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…From the literature reviews, preliminary results showed the power port to have a similar complication rate as conventional ports [32,33]. As the power port could serve as entry access for the chemotherapeutic agent and contrast medium, the frequency of venipuncture was much decreased, and the patients' satisfaction were higher than conventional port [34]. In our study, there was no contrast leak during power injection and may be correlated to the low body mass index of our study cohort.…”
Section: Discussionsupporting
confidence: 51%
“…From the literature reviews, preliminary results showed the power port to have a similar complication rate as conventional ports [32,33]. As the power port could serve as entry access for the chemotherapeutic agent and contrast medium, the frequency of venipuncture was much decreased, and the patients' satisfaction were higher than conventional port [34]. In our study, there was no contrast leak during power injection and may be correlated to the low body mass index of our study cohort.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies have con rmed that the merits of the TIVAD are a safe route to the central vein, long-term maintenance, and comfort for the patients in clinical application. [2][3][4][5] At the end of treatment, the removal of TIVADs is a basic and important procedure. Historically, removal of TIVADs is usually conducted by an interventional radiologist or a surgeon.…”
Section: Introductionmentioning
confidence: 99%